Konflik Lingkungan Dan Tanggung Jawab Hukum Terhadap Kerusakan Lingkungan dalam Kasus Lumpur Lapindo: Konflik Lingkungan dan Tanggung Jawab - Maharani Listi Putri Hariyanto; Dewi, Renny Nur Haliza; Puspa Pertiwi; Ria Tri Vinata (Faculty of Law, University of Muhammadiyaha Surabaya, 2025)
The Lapindo Mud Tragedy in Sidoarjo since 2006 is a major environmental disaster with widespread impacts, causing damage to land, settlements, and the socio-economic community. However, to date, its resolution remains fraught with controversy and injustice. This study aims to analyze the form of legal accountability carried out by PT Lapindo Brantas Inc. towards victims and evaluate law enforcement in this case. The approach used is normative legal research and field observation. It was found that PT Lapindo Brantas Inc. did not provide fair compensation to victims, and criminal law efforts were hampered by weak law enforcement and the tug-of-war of political and economic interests.